الخلاف حول واحة البريمي وأثرها على العلاقات السعودية الإماراتية بين عامي 1952-1955م (Journal of the College of Basic Education, 2026)
The research, entitled "The Buraimi War and Its Impact on Saudi-Emirati Relations between 1952 and 1955," includes an introduction and four chapters. It addresses the historical and geographical aspects of the Buraimi region, the political, strategic, and economic aspects of this region, the historical background of regional conflicts in the region prior to this war, and the conflicting parties and their interests therein. The second chapter covers the Buraimi War through the (direct) and indirect causes of the outbreak of the war, the events and developments, an analysis of the main events witnessed in the war, the role of regional and international powers in the conflict, and the short-term consequences and repercussions of this war. The third chapter covers the impact of the Buraimi War on Saudi-Emirati relations, an analysis of the official positions and reactions of both countries to the war, the impact of the war on the level of trust and cooperation between them in the subsequent period, the role of mediation and diplomatic efforts in containing the repercussions of the war, and the impact of the founding of the UAE on the course of relations. Finally, the fourth section explores overcoming the effects of the past to build strategic relations, the factors that contributed to overcoming the effects of the Buraimi War, the development of cooperation and coordination between Saudi Arabia and the UAE in various fields, and the role of common interests and regional challenges in strengthening relations as a model for relations between neighboring countries in the region. At the end of the research, there is a conclusion and a summary of the most important findings and the most prominent recommendations, as well as a list of the books used